Analysis of scientific and technological production about Digital Forensic Science - Silva, Wanderson de Vasconcelos Rodrigues da (2020)
The information age has brought more practicality in the way of dealing with data, increasing the use of technological resources. This new context has led to the emergence of new illegal activities such as digital crimes. In order to combat cybercrime, Forensic Science has evolved, with the addition of computer knowledge and the creation of the then Digital Forensic Science. To be successful in this mission, it is essential that Forensic Digital is always evolving and updating techniques through research and development of technological tools. With this work, the objective was to explore the current stage of scientific and technological development of Forensic Digital, by mapping the production of articles and patent deposits in the area. The Web of Science and Derwent Innovations Index databases were used to collect scientific and technological data, which were analyzed, giving them broader meanings, linked to the theoretical foundation. With the results it is pointed out that research has increased in the last decade with publications in several countries. However, there are still difficulties with the technologies, being developed mainly by individuals and companies. Thus, it is believed that the approximation between science and technology is essential for further advances in this area.